Bilateral synchronous adrenal metastases of renal cell carcinoma: A case report and review of the literature - ÖZTÜRK, HAKAN (Oncol Lett, 2015)
Renal cell carcinomas (RCCs) metastasize to the adrenal glands via various mechanisms, including lymphatic vessel arterial embolism and retrograde venous embolism. The rate of ipsilateral metastasis is 3–5% and the rate of contralateral metastasis is ~0.7%, however, synchronous bilateral adrenal metastases are extremely rare. Therefore, the optimal diagnosis and treatment strategy for this condition is yet to be thoroughly defined. In the present study, a 50-year-old male patient presented with right flank pain. Ultrasonography (US) revealed a right renal mass and bilateral adrenal metastases, and a computerized tomography (CT) scan determined the size of the lesions: An 86×83×66-mm mass in the lower pole of the right kidney, an 18×12×10-mm mass in the right adrenal gland, and a 69×51×53-mm mass in the left adrenal gland with central necrosis and peripheral contrast uptake. A US-guided biopsy was performed which determined a diagnosis of right RCC and bilateral synchronous adrenal metastasis. Immunohistochemical examination of the biopsy revealed clear cell carcinoma (Fuhrman grade, III). Consequently, right radical nephrectomy, right partial adrenalectomy (with frozen section examination) and left adrenalectomy were planned. The bilateral synchronous adrenal metastases posed a challenge in the diagnosis and treatment of the disease, as there is no standard approach in the literature for the treatment of such patients. However, metastasectomy was selected, as it appears to be the most effective treatment strategy for increasing the rate of cancer-specific survival. As an adrenal mass was present in the current patient, a hormonal examination was recommended and an adrenal-preserving minimally invasive surgical procedure using frozen section examination during surgery was particularly important to prevent the patient from developing adrenal insufficiency.